1993
DOI: 10.1007/bf00199751
|View full text |Cite
|
Sign up to set email alerts
|

Specific proteins in the sieve-tube exudate of Ricinus commuais L. seedlings: separation, characterization and in-vivo labelling

Abstract: Abstract. Ricinus communis L. seedlings exuded pure phloem sap from the cut hypocotyl for several hours. Throughout the entire exudation period proteins were present in the phloem exudate at a constant concentration ranging from 0.11 to 0.41 mg. ml 1 depending on the culture conditions and the age of the seedlings. Manipulation of the nutrient supply at the cotyledons after removal of the endosperm did not change the protein concentration in the exudate. Comparison of sieve-tube exudate proteins (STEPs) with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 35 publications
1
62
0
3
Order By: Relevance
“…The collective term "sieve tube exudate proteins," or STEPs, has been used to describe these unknown proteins (Sakuth et al, 1993), and labeling studies of STEPs obtained from Ricinus communis seedlings indicate that the proteins are synthesized continually. Because the exudates are obtained from mature enucleate sieve tubes, it seems likely that the proteins are synthesized in neighboring nucleated companion cells.…”
Section: Similar Data Have Been Obtained In the Analysis Of Sut7mentioning
confidence: 99%
“…The collective term "sieve tube exudate proteins," or STEPs, has been used to describe these unknown proteins (Sakuth et al, 1993), and labeling studies of STEPs obtained from Ricinus communis seedlings indicate that the proteins are synthesized continually. Because the exudates are obtained from mature enucleate sieve tubes, it seems likely that the proteins are synthesized in neighboring nucleated companion cells.…”
Section: Similar Data Have Been Obtained In the Analysis Of Sut7mentioning
confidence: 99%
“…More than 100 proteins, ranging in molecular weight from 10 to 90 kD, apparently move from CCs into the enucleate SE of the phloem, the long-distance photoassimilate transport system (Fisher et al, 1992;Nakamura et al, 1993;Sakuth et al, 1993). Because the mature SEs of the phloem lack nuclei and ribosomes and thus are incapable of protein synthesis, all macromolecules must be transported into SEs from neighboring CCs, presumably through PD (see Sjolund, 1997, in this issue).…”
Section: Plasmodesmal Transport Of Endogenous Plant Proteinsmentioning
confidence: 99%
“…Traditionally, they were thought to be able to permit only passive diffusion of small molecules, but recent studies have demonstrated that plasmodesmata can also mediate cell-to-cell trafficking of macromolecules such as proteins and nucleic acids of viral origin (Fujiwara et al, 1993;Noueiry et al, 1994;Ding et al, 1995Ding et al, , 1997Waigmann and Zambryski, 1995;Nguyen et al, 1996;Canto et al, 1997;Itaya et al, 1997;Rojas et al, 1997) and of plant origin (Bostwick et al, 1992;Fisher et al, 1992;Nakamura et al, 1993;Sakuth et al, 1993;Jackson et al, 1994;Ishiwatari et al, 1995;Lucas et al, 1995;Schobert et al, 1995;Perbal et al, 1996;Balachandran et al, 1997;Clark et al, 1997;Kü hn et al, 1997;Murillo et al, 1997). These findings indicate that intercellular trafficking of macromolecules through plasmodesmata is potentially an important means of coordinating developmental and physiological processes at the transcellular level Lucas, 1995;Mezitt and Lucas, 1996;Ding, 1997Ding, , 1998Jackson and Hake, 1997;Ding et al, 1998).…”
mentioning
confidence: 99%